A Thermo-Electrochemical Model of 18.5 V/50 Ah Battery Module for Railway Vehicles - Song, Jihun; Lee, Hyobin; Kim, Suhwan; Kang, Dongyoon; Jung, Seungwon; Lee, Hongkyung; Kwon, Tae-Soon; Lee, Yong Min (Frontiers in Materials, 2022)
We developed a thermo-electrochemical model of a 50 Ah pouch-type lithium-ion cell and utilized a cell model to build an 18.5 V/50 Ah module to analyze the thermal behavior under various operating conditions and design cooling systems for optimal operating temperature ranges. Specifically, the heat generated by electrochemical reactions was simulated through an electrochemical cell model, and then the calculated heat was coupled with a heat transfer model reflecting the actual 3D structure of the cell. By fitting two temperature-dependent parameters, i.e., the chemical diffusion coefficient and exchange current density, the model accurately estimated the electrochemical and thermal properties with errors less than 3%, even under wide temperature (25 ℃, 35 ℃, and 45 ℃) and C-rate (0.5C, 1C, 2C, and 5C) conditions. Based on this reliable cell model, we built an 18.5 V/50 Ah module model with five cells in series to simulate both the amount of heat generated and the required heat sink. Finally, both the cell and module models were used to predict the electrochemical and thermal behaviors under actual wireless tram operations in Turkey. The model results were compared with experimental results to confirm their reliability.